Analisis Partisipasi Politik Generasi Z Pada Pilpres 2024(Study Di Desa Karang Tapen) - Arwita Arwita; Neneng Mutmainnah; Nurul Izzati; Ulfatunnisah Ulfatunnisah; Wilandha Yasmin Ul Mizan; Zul Fiya Ayunia Jaelani; Edy kurniawansyah (Jurnal Sultra Elementary School, 2024)
This research analyzes the political participation of Generation Z in the 2024 Presidential Election in Karang Tapen Village, using a qualitative approach with a case study method. Data were obtained through in-depth interviews, participatory observation, and document analysis. The research results show a variation in the political participation of Generation Z, ranging from active to passive. Active Generation Z utilizes social media as a source of political information and group discussions to form critical views. However, some others only participate formally without delving into political issues. The main factors influencing their participation include the ease of access to digital information, the relevance of political programs, and social influence. Participation challenges include apathy, negative social media influence, and the tendency to abstain from voting. This research suggests more effective use of social media and campaigns relevant to the needs of Generation Z to increase their political participation. This study makes an important contribution to understanding the political dynamics of the younger generation in the context of local democracy.